2015
DOI: 10.1038/onc.2015.240
|View full text |Cite
|
Sign up to set email alerts
|

RhoB loss induces Rac1-dependent mesenchymal cell invasion in lung cells through PP2A inhibition

Abstract: Non-small-cell lung cancer (NSCLC) is the leading cause of cancer-related death worldwide, which is mainly due to its high risk of metastatic dissemination. One critical point of this process is the ability of cancer cells to detach from the primary tumor and migrate through the extracellular matrix; however, the underlying molecular mechanisms are not yet fully understood. In the present study, we identified the small GTPase RhoB as a key regulator of bronchial cell morphology in a three-dimensional (3D) matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 54 publications
7
49
0
Order By: Relevance
“…40 Mazieres et al 41 found that the level of the RhoB protein dramatically decreased over the course of lung cancer progression and was lost in 96% of invasive tumors, whereas the ectopic expression of RHOB in the lung cancer cell line A549 suppressed cell proliferation both in vitro and in vivo. Moreover, RhoB loss could induce Rac1-dependent mesenchymal cell invasion in lung cells through the control of PP2A activity, 29 and promote the invasion of human bronchial cells via the activation of AKT1. 42 Furthermore, Mazieres et al 43 also reported that the loss of RhoB expression was induced via epigenetic regulation by histone deacetylation in lung cancer, whereas we found that LSD1 recruited by DUXAP8-mediated histone demethylation also contributed to RHOB loss of expression in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Mazieres et al 41 found that the level of the RhoB protein dramatically decreased over the course of lung cancer progression and was lost in 96% of invasive tumors, whereas the ectopic expression of RHOB in the lung cancer cell line A549 suppressed cell proliferation both in vitro and in vivo. Moreover, RhoB loss could induce Rac1-dependent mesenchymal cell invasion in lung cells through the control of PP2A activity, 29 and promote the invasion of human bronchial cells via the activation of AKT1. 42 Furthermore, Mazieres et al 43 also reported that the loss of RhoB expression was induced via epigenetic regulation by histone deacetylation in lung cancer, whereas we found that LSD1 recruited by DUXAP8-mediated histone demethylation also contributed to RHOB loss of expression in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…EGR1 and RHOB are newly identified tumor suppressors, and their loss is frequently observed during lung cancer development and progression. 29,30 Therefore, we assumed that DUXAP8 contributes to NSCLC by repressing EGR1 and RHOB expression. Accordingly, we used western blot analysis to examine their protein levels in H1299 and H1975 cells transfected with DUXAP8 or control siRNA.…”
Section: Egr1 and Rhob Are Key Downstream Targets Of Duxap8 In Nsclc mentioning
confidence: 99%
“…12), tumorigenic epithelial cell lines BEAS-2B, cancer-derived cell lines A549 and H1975 from ATCC, and BEAS-2B-KRasV12 from Dr. Pradines (9,13) were grown in supplemented appropriate media (Supplementary Table S1), transfected at 30% confluence, using Lipofectamine RNAiMAX (Invitrogen) with siRNA, plasmid DNA, or control mimics (Dharmacon; Supplementary Tables S2 and S3). HBEC-3 and HBEC-3-KRasG12V were authenticated using standard karyotyping techniques as previously described (12).…”
Section: Methodsmentioning
confidence: 99%
“…S8E), and we hypothesized that such phosphatase regulation could influence GEFH1 phosphorylation state. Recently, siRNA-mediated depletion of RhoB was reported to downregulate PP2A activity (13). By immunoprecipitating PP2ACa from cells lysates derived from BEAS2B cells expressing RASSF1A, we detected both GEFH1 and RhoB with specific antibodies (Supplementary Fig.…”
Section: Rassf1a Controls Activation Of the Cofilin Pathwaymentioning
confidence: 99%
See 1 more Smart Citation